2009
DOI: 10.3109/00365520903453182
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, pilot study of geranylgeranylacetone versus placebo in patients taking low-dose enteric-coated aspirin. Low-dose aspirin-induced small bowel damage

Abstract: Objective. Low-dose enteric-coated aspirin is increasingly being used for prevention of cardiovascular disease. The aim of this study was to evaluate whether geranylgeranylacetone (GGA) could prevent aspirin-induced small bowel injury. Material and methods. This was a prospective, randomized, double-blind, pilot study of GGA versus placebo in subjects taking low-dose enteric-coated aspirin. Young healthy volunteers were enrolled and each received 100 mg of enteric-coated aspirin per day plus either GGA (150 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
60
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 34 publications
1
60
1
3
Order By: Relevance
“…Nevertheless data on peptic ulcer patients are limited [12] . In our study, prevalence of small bowel ulcerative lesions in NSAID users with non-bleeding peptic ulcer equals the mean of medical literature for non-ulcer NSAIDs consumers [1,23,[25][26][27] , even that reported by our group for NSAID consumers with iron deficiency anemia [13] . On the contrary, prevalence of small bowel ulcerative lesions was much higher among NSAID consumers with peptic ulcer bleeding.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Nevertheless data on peptic ulcer patients are limited [12] . In our study, prevalence of small bowel ulcerative lesions in NSAID users with non-bleeding peptic ulcer equals the mean of medical literature for non-ulcer NSAIDs consumers [1,23,[25][26][27] , even that reported by our group for NSAID consumers with iron deficiency anemia [13] . On the contrary, prevalence of small bowel ulcerative lesions was much higher among NSAID consumers with peptic ulcer bleeding.…”
mentioning
confidence: 54%
“…Nevertheless recent reports suggest that proton pump inhibitors could exacerbate small bowel ulcerative lesions [22] . Small bowel ulcerative lesions are more frequent in reports including chronic NSAID consumers [1,23] than those including healthy volunteers who received NSAIDs short-term [8,[23][24][25][26] . A head to head comparison in our study revealed no difference between short and long-term NSAID consumers with concurrent peptic ulcer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Прием мизопростола 200 мкг 4 раза в день в течение 8 нед оказался эффективен при лечении индуцированной АСК энтеропатии [48]. Помимо аналогов про-стагландинов разрабатываются и апробируются другие химиче-ские соединения с цитопротективной активностью в тонкой киш-ке (Rebamipide, Teprenone, Polaprezinc, Irsogladine maleate), но по-ка они доступны только в нескольких азиатских странах [49][50][51].…”
Section: терапевтический архив 12 2014unclassified
“…3,4,[6][7][8][9][10][11]15,[18][19][20][21][22][23][24][25][26] However, in most studies, the primary endpoint was smallbowel mucosal injury, and the outcomes did not include smallbowel overt bleeding. In addition, these studies had small sample sizes, and half of them included healthy subjects and nonhospital-based patients.…”
mentioning
confidence: 99%